The ecological uncertainty of wildfire fuel breaks: examples from the sagebrush steppe. Issue 5 (6th May 2019) - Shinneman, Douglas J; Germino, Matthew J; Pilliod, David S; Aldridge, Cameron L; Vaillant, Nicole M; Coates, Peter S
Abstract : Fuel breaks are increasingly being implemented at broad scales (100s to 10, 000s of square kilometers) in fire‐prone landscapes globally, yet there is little scientific information available regarding their ecological effects (eg habitat fragmentation). Fuel breaks are designed to reduce flammable vegetation (ie fuels), increase the safety and effectiveness of fire‐suppression operations, and ultimately decrease the extent of wildfire spread. In sagebrush ( Artemisia spp) ecosystems of the western US, installation of extensive linear fuel breaks is also intended to protect habitat, especially for the greater sage‐grouse ( Centrocercus urophasianus ), a species that is sensitive to habitat fragmentation. We examine this apparent contradiction in the Great Basin region, where invasive annual grasses have increased wildfire activity and threaten sagebrush ecosystems. Given uncertain outcomes, we examine how implementation of fuel breaks might (1) directly alter ecosystems, (2) create edges and edge effects, (3) serve as vectors for wildlife movement and plant invasions, (4) fragment otherwise contiguous sagebrush landscapes, and (5) benefit from scientific investigation intended to disentangle their ecological costs and benefits.